(untitled) (Scientific journal of the Fergana State University, 2026)
This article presents the modern methodological foundations for improving the professional-practical physical training of students at the Faculty of Military Education. In the course of the study, a block-modular system was applied for the effective organization of training sessions, which allowed for the step-by-step development of students’ physical training, motor skills, and professional-applied competencies. The conducted pedagogical experimental research demonstrated that structuring the educational process based on mesocycles and microcycles ensures its continuity, systematic approach, and purposefulness. The results of the experiment confirmed that the implementation of the block-modular system contributes significantly to the development of students’ physical qualities (strength, endurance, agility, speed, and coordination), as well as enhancing their readiness for professional activities. Based on the obtained data, the high effectiveness of the proposed methodology in the implementation of educational courses within the military education system has been proven.